Response of sugarcane ratoons to nitrogen rates and methods of application in Guneid Sugar Scheme, Sudan - Mukhtar, Salaheldin (Gezira Journal of Agricultural Science, 2015)
Three experiments were conducted during the periods 2007 to 2013 at the farm of the Sugarcane Research Center-Guneid (SCRCG), Sudan. The objective was to investigate the response of sugarcane ratoon crops to different rates of nitrogen in the form of urea in addition to splitting the rate during the long season of sugarcane crop. The first experiment included 150, 200 and 250 kg urea/feddan            (feddan, f=4200m 2 ). Treatments in the second experiment were zero, 50, 100, 150 and 200 kg urea/ f, while the third experiment consisted of zero, 100, 150, 175 and 200 kg urea/f, for the first, second and third ratoons. The treatments of the second experiment were coupled with splitting the dose of urea versus the full dose       (two thirds at the age of 20 to 30 days; and one third at the age of three to four months). Treatments were laid out in a randomized complete block design with four replicates in experiment I and III and a factorial arrangement for experiment II with four replicates. The results revealed that there were no significant differences in yield components and total cane yield of the ratoon crop between the rates of nitrogen of the first experiment. In the second experiment, yield components and total cane yield increased significantly for rates of urea from zero to 100, 50 to 150 and 100 to 200 kg urea/ f. In the third experiment, only cane yield increased with the increase of N rate but significant only between zero and 150 to 200 kg urea/f in the first ratoon, zero and 100 to 200 kg urea /f in the second ratoon, and zero and 100; 100 and 150 to 200 kg urea/f in the third ratoon. Brix, pol% cane and ERS%, decreased significantly with the increased rate of N in all experiments. No significant differences in yield and quality parameters were found in response to splitting the rate of N. The rates of 150 and 200 kg urea/f seemed satisfactory for both cane and sugar yields for the ratoon crops.  However, under field conditions where many factors interact it is seen as advisable to have some N reserves. In this sense, 200 kg urea /f is recommended as the dose to be endorsed as an official dose for the ratoon crops in the Guneid Sugar Scheme. أجريت ثلاث تجارب (I وII و III) بمزرعة مركز بحوث قصب السكر- الجنيد، السودان خلال المواسم 2007 إلى 2013. هدفت الدراسة لبحث إستجابة محاصيل خلف قصب السكر لجرعات مختلفة من السماد الآزوتى (النيتروجين) في شكل يوريا، إضافة لتقسيم الجرعات خلال الموسم الطويل لقصب السكر. تضمنت التجربة الأولى الجرعات150 و200 و250 كجم يوريا للفدان (الفدان=4200م 2 ). وكانت معاملات التجربة الثانية صفر و50 و100 و150 و200 كجم يوريا للفدان. بينما كانت معاملات التجربة الثالثة 100 و150 و175 و200 كجم يوريا للفدان. أجريت كل التجارب للخلفة الأولى والثانية والثالثة. أضيفت معاملة تقسيم الجرعة إلى معاملات التجربة الثانية حيث أضيفت ثلثا الجرعة في عمر خلفة القصب من 20 إلى 30 يوم و أضيف الجزء الأخير من الجرعة في عمر 3 إلى 4 شهور. وقد أستخدم تصميم القطاعات العشوائية الكاملة مع أربعة مكررات في التجربة I وIII وتصميم عاملين بأربعة مكررات للتجربة II. أبانت النتائج عدم وجود إختلافات معنوية في إنتاجية القصب ومكوناتها لجرعات اليوريا 150 و200 و250 كجم للفدان للخلفة الأولى والثانية والثالثة للتجربة الأولى. وفي التجربة الثانية، زادت إنتاجية القصب  ومكوناتها معنويا بزيادة الجرعة من صفر إلى 50 و100 و150 و200 كجم يوريا للفدان.  بينما زادت فقط إنتاجية القصب في التجربة الثالثة بزيادة جرعة اليوريا ولكن كانت الزيادة معنوية فقط بين جرعة صفر و150 إلى 200 كجم للفدان في الخلفة الأولى، وبين صفر و100 إلى 200 كجم للفدان في الخلفة الثانية، وبين صفر و100 كجم للفدان، وبين 100 و150 و200 كجم للفدان في الخلفة الثالثة. نقصت مؤشرات جودة قصب السكر بصورة معنوية و أحيانا بصورة غير معنوية، بزيادة جرعة اليوريا بصورة عامة في كل الدراسة. لم تحدث فروقات معنوية في مكونات جودة وإنتاجية القصب في معاملة تقسيم الجرعة مقارنة مع إضافتها كاملة. في هذه الدراسة بدت الجرعتان 150 و 200 كجم يوريا للفدان مناسبتان لإنتاجية القصب والسكر لخلفات قصب السكر. إلا أنه في ظروف الحقل تتداخل عوامل كثيرة و يعتقد أنه من  الأوفق أن يكون هنالك زيادة إحتياطية من عنصر السماد النيتروجيني. وعليه يوصى بتبني جرعة 200 كجم يوريا للفدان لتطبق أساساً على محاصيل خلفات قصب السكر في مشروع سكر الجنيد بالسودان.